Attribution Model of Travel Intention to Internet Celebrity Spots: A Systematic Exploration Based on Psychological Perspective - Kui Yi; Qingqing Wang; Jun Xu; Bin Liu (Frontiers in Psychology, 2021)
Previous studies have shown that the empathy process is the main driving factor that triggers tourists’ intention to visit Internet celebrity spots. However, the academic community has not yet formed a unified understanding of the concrete mechanism. Based on this, this study combines the connotations of meme theory and empathy theory and applies Structural Equation Modeling (SEM) to empirically analyze 340 valid samples of Internet celebrity spots visitors to explore the influence mechanism of attributional factors on travel intention. The result shows that mechanism of travel intention can be presented as a psychological model in which travel attribution of tourists to visit Internet celebrity spots is the independent variable, the travel intention is the dependent variable, and the empathy process is the intermediary variable. The influence intensity of internal attribution on affective empathy is higher than that of external attribution, while the influence intensity of external attribution on cognitive empathy has a comparative advantage, and there is a significant difference between them. Empathy process has a significant mediating effect on the relationship between travel attribution and travel intention of tourists to visit Internet celebrity spots, and the mediating effect of affective empathy is significantly greater than that of cognitive empathy. Overall, this study reveals the segmentation elements with strong explanatory power in the behavior of “internet celebrity spots punch in,” examines the practical effect of empathy process in the behavioral intention of traveling, and provides a theoretical reference for the transformation and upgrading of tourist destinations and marketing planning of online communication in the future.